Blurring Northeast Mexican Societies: An Approach to Cultural Capital and Results of the PISA Test - Pérez Maldonado, Mónica Mendirichaga (2019)
The present research shows, from the results of the PISA Test of the years 2012-2015, the difference that exists in the societies of the northeast, comparing the state of Nuevo León with the states of Coahuila, San Luis Potosí and Tamaulipas. It seeks to evaluate the field of reading in each of these regions,coupled with the results of mathematics and science. Taking from the PISA Test 38,251 records, those of these four states are included, giving a total of 4,764 records. For the above, it is basic what is related to the reading process and the existence of libraries, as well as other exogenous variables, all this done through the software of the Weka 3.9.2 program